Decision-making in the conditions of introduction of automated design systems of technological processes in enterprises of oil machine building - Bogatenkov, S. A.; Sazonova, N. S.; Abbasova, H. M.; Badalova, B. B.; Bazhenov, R. I.; Yusubov, Nizami (Oil Gas Scientific Research Project Institute, 2022)
To ensure the effectiveness of professional activities in the face of increasing requirements for the scope of design work and production preparation time, computer-aided design of technological processes (CAD TP) systems are used. However, there is a problem of safe implementation of CAD TP. The aim of the study is to develop a decision-making methodology for adapting CAD TP to the conditions of enterprises and to the work of personnel based on a systematic approach to threat analysis. The methodology includes methods for choosing CAD TP, using text and graphic prompts when entering information, as well as applying methods for unifying various CAD systems and adapting them to enterprise conditions at the database level. The results of the study are implemented in CAD for operations performed on multi-spindle horizontal automatic lathes and are used at South Ural State University and Azerbaijan Technical University.